Multiple effect of thermal treatment approach on PVDF membranes: Permeability enhancement and silver nanoparticles immobilization. Issue 4 (August 2021) - Kamarudin, Diyana; Awanis Hashim, N.; Ong, Boon Hoong; Kakihana, Yuriko; Higa, Mitsuru; Matsuyama, Hideto
Abstract: Impregnation of the noble metal, silver nanoparticles (AgNPs) as a disinfectant into the polymeric membrane is one of the empirical modification methods in producing safe drinking water. However, the dispersion and immobilization of AgNPs during membrane fabrication and application is least discussed despite numerous leaching phenomena reported. In this study, silver nanoparticles type 1 (AgNPs-1) and type 2 (AgNPs-2) were prepared and incorporated into polyvinylidene fluoride (PVDF) ultrafiltration membrane with the presence of thermal treatment. The effect of thermal treatment was studied at temperature 25 °C, 40 °C and 55 °C which significantly influenced the physicochemical characteristics of the PVDF membrane. Membrane incorporated with AgNPs-1 and AgNPs-2 fabricated at highest temperature portrayed improved mechanical properties and pure water flux. PVDF/PVP/AgNPs-2 membrane released the smallest amount of Ag (3.81%) while PVDF/PVP/AgNPs-1 cast at 40 °C released the largest amount of Ag (42.34%) during the phase inversion at fabrication. Notably, no Ag leaching was found in all membranes during the dead-end filtration at 0.5 bar. Membranes with AgNPs-1 and AgNPs-2 showed remarkable bactericidal performance towards E. coli with a percentage reduction of 90.38% and 80.77%, respectively. Thus, membranes with AgNPs fabricated at 55 °C offered better mechanical properties of the enhanced permeability and excellent stability of AgNPs immobilization which signified the thermal treatment approach. Graphical Abstract: ga1 Highlights: PVDF membranes incorporated with AgNPs were fabricated at elevated temperature for facile thermal treatment approach. Membranes fabricated with thermal treatment approach have enhanced permeability and immobilized AgNPs. Leaching phenomena AgNPs were analysed using ICP-OES, XPS and TGA. Bactericidal properties were quantitatively analysed using bacteria count plate towards S.aureus and E.coli